“Salus Populi Suprema Lex”: Considerations on the Initial Response of the United Kingdom to the SARS-CoV-2 Pandemic - Favi, Evaldo; Leonardis, Francesca; Manzia, Tommaso Maria; Angelico, Roberta; Alalawi, Yousof; Alfieri, Carlo; Cacciola, Roberto (Frontiers in Public Health, 2021)
In several countries worldwide, the initial response to coronavirus disease 2019 (COVID-19) has been heavily criticized by general public, media, and healthcare professionals, as well as being an acrimonious topic in the political debate. The present article elaborates on some aspects of the United Kingdom (UK) primary reaction to SARS-CoV-2 pandemic; specifically, from February to July 2020. The fact that the UK showed the highest mortality rate in Western Europe following the first wave of COVID-19 certainly has many contributing causes; each deserves an accurate analysis. We focused on three specific points that have been insofar not fully discussed in the UK and not very well known outside the British border: clinical governance, access to hospital care or intensive care unit, and implementation of non-pharmaceutical interventions. The considerations herein presented on these fundamental matters will likely contribute to a wider and positive discussion on public health, in the context of an unprecedented crisis.